DAMPAK KENAIKAN HARGA KEDELAI DUNIA DAN PENGHAPUSAN TARIF IMPOR KEDELAI TERHADAP KESEJAHTERAAN MASYARAKAT - Wisnu Winardi (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2013)
The drought sufferd by saybean producing countries has coused an increase in world saybean price in 2012. Such condition resulted in unrest among various domestic companies since the majority of saybean consuption in indonesian is fulfilled through importation. This research is performed to analyze the impact of increased price of world saybean on the people’s welfore using the hicksin equivalent variation (EV) derived from the result of simultion uing static CGE model. This research also simulates the same shocking impact on the real importations, composite price, households consumptions and government income. Based on the result of simulation, the increase in world saybean price is estimated to decrease the real import of saybean and soy-related commodities in general, increase the composite price, reduse households consumption and welfore and increase the government income , the saybean importation tarif elimination policy adopted as a response to the 5% increase in world saybean price is estimated to reduse the real importation , reduse composite price, increase the households consumption and welfare and decrease the government income, whereas the same policy adopted as response to the 10 % and 15% increase in world saybean price is estimated to reduse the real importation, prevent price increase, reduse households consumption and welfare and reduce the government.